1954. Immunogenicity against SARS CoV-2 ancestral strain and variants of two new COVID-19 recombinant adjuvanted vaccines compared to BNT162b2 as a third dose following two doses of BNT162b2: a single-blinded multicenter randomized controlled trial. (15th December 2022) - Launay, Odile; Cachanado, Marine; Luong, Liem Binh; Ninove, Laetitia; Lachâtre, Marie; Ghezala, Inès Ben; Bardou, Marc; Schmidt-Mutter, Catherine; Lacombe, Karine; Laine, Fabrice; Allain, Jean-Sébastien; Botelho-Nevers, Elisabeth; et al.
Abstract: Background: New adjuvanted recombinant protein vaccines against coronavirus disease 2019 (COVID-19) as heterologous boosters could maximize the benefits of vaccination against SARS CoV-2. Methods: In this randomized, single-blinded, multicenter trial, adults who had received two doses of Pfizer-BioNTech mRNA vaccine (BNT162b2) 3–7 months before were randomly assigned to receive a boost of BNT162b2, Sanofi/GSK SARS-CoV-2 adjuvanted recombinant protein MV D614 (monovalent parental formulation) or SARS-CoV-2 adjuvanted recombinant protein MV B.1.351 vaccine (monovalent Beta formulation). The primary endpoint was the percentage of subjects with a ≥ 10-fold increase in neutralizing antibody titers for the Wuhan (D614) and B.1.351 (Beta) SARS-CoV-2 viral strains between D0 and D15. Results: The percentages of participants whose neutralizing antibody titers against the Wuhan (D614) SARS-CoV-2 strain increased by a factor ≥ 10 between Day 0 and Day 15 was 55.3% (95% CI 43.4-66.7) in MV(D614) group (n=76), 76.1% (64.5-85.4) in MV(Beta) group (n=71) and 63.2% (51.3-73.9) in BNT162b2 group (n=76). These percentages were 44.7% (33.3-56.6), 84.5% (74.0-92.0) and 51.3% (39.6-63.0) for the B.1.351 (Beta) viral strain, respectively. Higher neutralizing antibodies rates against Delta and Omicron BA.1 variants were also elicited after Sanofi/GSK MV(Beta) vaccine compared to the other vaccines. Comparable reactogenicity profile was observed the three vaccines. Table 1. Characteristics of patients at inclusion (per-protocol population). Figure 2. Neutralizing antibodies against D614 (wild-type; Wuhan) SARS-CoV-2 and variants Beta, Delta and Omicron BA.1 at D0, D15 and D28 after the boost dose ("post D3")with Sanofi/GSK-D614, Sanofi/GSK-B.1.351 or BNT162b2 (per-protocol population); dotted line represents the positivity threshold. Figure 4. Rates and grades of severity of solicited adverse events reported from D0 to D7 by participants from the three randomized groups of the safety population (G1, Sanofi/GSK-D614; G2, Sanofi/GSK-B.1.351; G3, BNT162b2) according to the Toxicity Grading Scale for Healthy Adult and Adolescent Volunteers Enrolled in Preventive Vaccine Clinical Trials (Modified FDA scale/September 2007) Conclusion: All three vaccines boosted antibodies and neutralizing response after BNT162b2 initial course. Heterologous boosting with the Sanofi/GSK SARS-CoV-2 adjuvanted recombinant protein vaccine B.1.351 (Beta formulation) provided higher neutralizing antibodies response rates against variants, including Omicron BA.1, compared with the mRNA BNT162b2 vaccine. Disclosures: Odile Launay, MD, PhD, AstraZeneca: Financial|GlaxoSmithKline: Advisor/Consultant|GlaxoSmithKline: Grant/Research Support|Johnson & Johnson: Advisor/Consultant|Johnson & Johnson: Grant/Research Support|MD: Advisor/Consultant|Moderna: Advisor/Consultant|MSD: Data safety monitoring board|Pfizer: Advisor/Consultant|Pfizer: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant|Sanofi Pasteur: Grant/Research Support|Sanofi Pasteur: Data safety monitoring board Liem Binh Luong, MD, Pfizer: Advisor/Consultant|Pfizer: Honoraria Karine Lacombe, MD, PhD, Gilead: Advisor/Consultant|Janssen: Grant/Research Support|MSD: Grant/Research Support|ViiV Healthcare: Grant/Research Support Elisabeth Botelho-Nevers, MD, PHD, Janssen: Board Member|Pfizer: Board Member|Sanofi Pasteur: Board Member.